2012
DOI: 10.1590/s0004-28032012000100009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of upper digestive endoscopy and gastric histopathology findings in morbidly obese patients

Abstract: -Context -The prevalence of obesity has been increasing in modern society. Roux-en-y gastric bypass is a bariatric surgery that involves the exclusion of significant part of the stomach.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

4
15
0

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(19 citation statements)
references
References 34 publications
4
15
0
Order By: Relevance
“…A systematic review has shown that the prevalence of H. pylori in obese patients scheduled to undergo bariatric surgery varies from 6.9-61.3%. The prevalence of infection caused by this pathogen varies from 30 to 90% around an average of 60% 7 .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…A systematic review has shown that the prevalence of H. pylori in obese patients scheduled to undergo bariatric surgery varies from 6.9-61.3%. The prevalence of infection caused by this pathogen varies from 30 to 90% around an average of 60% 7 .…”
Section: Discussionmentioning
confidence: 99%
“…H. pylori infection causes inflammation of the gastric mucosa and may lead to problems such as intestinal metaplasia and even cancer. Its eradication may revert this inflammatory process but this is not possible in more advanced phases 7 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Many guidelines recommend routine endoscopy but many of Numbers in brackets are the 95 % confidence intervals these were published prior to sleeve gastrectomy becoming an established bariatric procedure [15]. Furthermore, it has previously been demonstrated that pre-operative gastroscopy findings do not correlate well with histopathologic findings and would uncommonly alter the surgical management when a sleeve gastrectomy is intended [7,16,17]. As sleeve gastrectomy does not make duodenal access more difficult and does not leave an in situ gastric remnant, the argument for routine pre-operative gastroscopy for sleeve gastrectomy is less strong than for gastric bypass.…”
Section: Discussionmentioning
confidence: 99%
“…A high prevelance of lower esophageal sphincter (LES) incompetency and hiatal hernia secondary to increased intraabdominal pressure frequently leads to GERD symptoms in obese persons (7). Despite the many studies in the lit-erature, the relationship between obesity and gastroesophageal sphincter incompetency (GSI) and H. pylori infection has not been fully clarified (7)(8)(9)(10).…”
Section: Introductionmentioning
confidence: 99%